Cost-aware strategies for enhancing energy resilience in microgrids via stationary and mobile resources - S.M. Safayet Ullah; Kouhyar Sheida; Farzad Ferdowsi; Terrence Chambers (Journal of Safety Science and Resilience)
The primary goal of this research study is to enhance energy resilience with a focus on cost efficiency. To achieve this objective, two key objectives have been identified: (1) reducing unserved loads, and (2) implementing cost-effective resource allocation strategies. A high-fidelity detailed model of a solar plus storage microgrid is developed to simulate a variety of what-if scenarios. This model is based on the conceptual design of a campus microgrid facility, which is slated for commissioning at UL Lafayette in close collaboration with a local power utility. The study examines the microgrid’s performance under different configurations, including both stationary battery and mobile battery storage options. To ensure the realism of the scenarios, real solar data from specific days following the occurrence of three major hurricanes in Louisiana is utilized. The analysis includes an assessment of unserved loads under various scenarios, as well as an investigation into the resilience impact of investment decisions and the planning and operation of mobile storage systems. The results indicate the proposed planning and operation will improve resilience while staying within the profitable range. The resilience is quantified and compared with other scenarios providing an insightful planning framework for decision-makers.